Pengembangan Handout Elektronik Menggunakan Flip PDF Professional pada Materi Kingdom Plantae sebagai Bahan Ajar Kelas X SMA/MA - Latifah Turrohmah; Nasrul Hakim (Jurnal Biotek, 2022)
In the teaching and learning process, teachers often teach using printed books, modules, worksheets, using LCD projectors, and have never combined printed teaching materials with electronic media. Based on the needs analysis questionnaire data given to students of class X MIA at SMAN 6 Metro, as many as 63.3% who have difficulty learning the material Kingdom Plantae. Thus, innovation is needed in the form of electronic handout teaching materials. This study aims to develop Electronic Handouts using Flip PDF Professional on Kingdom Plantae Materials as Teaching Materials for Class X SMA/MA. This type of research is an R&D (Research and Development) research with the ADDIE model which consists of five stages, namely Analysis-Design-Development-Implementation-Evaluate. The final result of Electronic Handout validation using Flip PDF Professional on Kingdom Plantae Materials as Teaching Materials for Class X SMA/MA obtained a percentage of 85.3% in the "very feasible" category by material expert validators and media expert validators obtained a percentage of 94.6% with "very decent" category. The results of the teacher trial obtained a percentage of 90% in the "very good" category and the results of the student trial obtained a percentage of 83.4% in the "good" category. Based on the overall results, the percentage of electronic handout scores obtained an overall average with a percentage of 88.32% and is included in the "Very Valid" category, and is suitable for use in the Biology learning process at school.